Dokumentiranje kulturne dediščine - Grobovšek, Jon (Knjižnica, 2012)
This article presents the process of documenting the cultural heritage from the beginning, the preparations for the documentation, to the final stage, the archiving of documents and its complementation. What, why and how are the questions which have to be answered during the process of documenting in order to carry out the process in an optimal fashion and conclude it with the desired outcomes. Different approaches to documenting and various ways have their own demands for realization and lead to different results. When documenting the cultural heritage we must be familiar with all the procedures,so that we are able to select the appropriate ones. The emphasis is on making architectural recording, photo shooting, recording of accompanying data and archiving the final accomplishments.
Keywords: cultural heritage; kulturna dediščina; documenting; dokumentiranje; architectural record; arhitekturni posnetki; photography; fotografija